2015
DOI: 10.1128/jvi.00825-15
|View full text |Cite
|
Sign up to set email alerts
|

Measles Virus Infection Inactivates Cellular Protein Phosphatase 5 with Consequent Suppression of Sp1 and c-Myc Activities

Abstract: Measles virus (MeV) causes several unique syndromes, including transient immunosuppression. To clarify the cellular responses to MeV infection, we previously analyzed a MeV-infected epithelial cell line and a lymphoid cell line by microarray and showed that the expression of numerous genes was up-or downregulated in the epithelial cells. In particular, there was a characteristic comprehensive downregulation of housekeeping genes during late stage infection. To identify the mechanism underlying this phenomenon,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Our previous study demonstrated that MeV induces characteristic comprehensive downregulation of housekeeping genes in epithelial cells [ 13 , 14 ] (Data set: [ 15 ]). We first assigned each downregulated gene to a cellular component group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study demonstrated that MeV induces characteristic comprehensive downregulation of housekeeping genes in epithelial cells [ 13 , 14 ] (Data set: [ 15 ]). We first assigned each downregulated gene to a cellular component group.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our previous study using microarray analysis revealed that many genes, including antiviral factors, are upregulated [ 13 ]. Interestingly, downregulation of numerous genes, especially housekeeping genes, has also detected during the late stage of infection [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, in our study we also found down-regulation of SP1 in CDV-infected MCF-7 cell line, indicating the role of CDV in silencing of SP1 protein and thus abolishing the activity of proliferation and progression of ductal breast tumor cells. Additionally, Measles virus (member of Pyromixiviridae family) is also reported to be down-regulating the activity of SP1 [27]. On the contrary, SP1 was found to be up-regulated in human cytomegalovirus infection indicating the differential effect on SP1 by different families of virus [28].…”
Section: Discussionmentioning
confidence: 99%